Sulphur and Boron Fertilization Increased Productivity of Boro Rice (BRRI dhan28) by Increasing Pollen Fertility and Agronomic Efficiency in Calcareous Soils - AKM Abdul Bari; Razita Jalil Promi; Imam Muhyidiyn; Moaz Hosen Pramanik; Cihan Demir; Murat ERMAN; Fatih ÇIĞ; Mohammad Sohidul Islam (ISPEC Journal of Agricultural Sciences, 2023)
To study the effect of sulphur (S) and boron (B) on the performance of yield, agronomic efficiency, economic return of boro rice (cv. BRRI dhan28) was evaluated at the Reseahc Field of the Department of Crop Science and Technology, University of Rajshahi, Rajshahi-6205, during the Rabi season from November 2015 to April 2016 in High Ganges River Floodplain under AgroEcological Zone-11 (AEZ-11). The experiment was consisted three level of sulphur, viz., S0: without sulphur (control), S20: 20 kg S ha-1, S30: 30 kg S ha-1, and three level of boron viz., B0: without boron (control), B2: 2 kg B ha-1, B3: 3 kg B ha-1. The experiment was conducted in a Randomized Complete Block Design (RCBD) with three replications. The results revealed that S and B significantly influenced the yield straw yield, biomass yield, sterility percentage, agronomic efficiency and economic return of BRRI dhan28. The treatment combination of S20B2 (20 kg S ha-1 with 2 kg B ha-1) performed the best results of the aforesaid traits. So, it can be suggested to apply S at 20 kg ha-1 and B at 2 kg ha-1 with recommended dose of NPK and Zn for maximizing yield, agronomic efficiency and economic point of view of boro rice in calcareous soils of AEZ-11.